2014
DOI: 10.1002/cmdc.201300480
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Human Soluble Adenylate Cyclase Reveals a Distinct, Highly Flexible Allosteric Bicarbonate Binding Pocket

Abstract: Soluble adenylate cyclases catalyse the synthesis of the second messenger cAMP through the cyclisation of ATP and are the only known enzymes to be directly activated by bicarbonate. Here, we report the first crystal structure of the human enzyme that reveals a pseudosymmetrical arrangement of two catalytic domains to produce a single competent active site and a novel discrete bicarbonate binding pocket. Crystal structures of the apo protein, the protein in complex with α,β-methylene adenosine 5′-triphosphate (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 54 publications
0
34
0
Order By: Relevance
“…At present, the PDB provides 28 sAC crystal structures (Kleinboelting et al, 2014a(Kleinboelting et al, ,b, 2016Saalau-Bethell et al, 2014;RamosEspiritu et al, 2016), including complexes with ATP, a,b-methylene adenosine-59-triphosphate, cAMP, pyrophosphate, bicarbonate, biselenite, bisulfite, bithionol, and various inhibitors. Comparing structures of 5C1: 2C2, of sAC-C1-C2 and of an inactive human sGCa cat : sGCb cat heterodimer (Allerston et al, 2013;Seeger et al, 2014) indicates high structural homology not only of the individual catalytic domains, but also of the whole complexes, and points to a common, well conserved mechanism of cNMP generation facilitated by two metal ions.…”
Section: From Organs To Purified Adenylyl Cyclasesmentioning
confidence: 99%
“…At present, the PDB provides 28 sAC crystal structures (Kleinboelting et al, 2014a(Kleinboelting et al, ,b, 2016Saalau-Bethell et al, 2014;RamosEspiritu et al, 2016), including complexes with ATP, a,b-methylene adenosine-59-triphosphate, cAMP, pyrophosphate, bicarbonate, biselenite, bisulfite, bithionol, and various inhibitors. Comparing structures of 5C1: 2C2, of sAC-C1-C2 and of an inactive human sGCa cat : sGCb cat heterodimer (Allerston et al, 2013;Seeger et al, 2014) indicates high structural homology not only of the individual catalytic domains, but also of the whole complexes, and points to a common, well conserved mechanism of cNMP generation facilitated by two metal ions.…”
Section: From Organs To Purified Adenylyl Cyclasesmentioning
confidence: 99%
“…It was subsequently shown that L-serine binding to this allosteric site activates PKM2. Finally, the allosteric bicarbonate binding site of human soluble adenylate cyclase (SolAC) was also characterized using X-ray crystallography (20,21), and a subsequent fragment screen against this target identified inhibitors that occupy this site.…”
Section: Significancementioning
confidence: 99%
“…Taken together, these findings suggest that sAC can be considered as a putative metabolic sensor. Recently the crystal structure of human sAC apo state was described [8, 9], including the mechanism of catalysis and the binding site of the HCO 3 − activation and regulators. The structure shows how HCO 3 − binds and activates sAC and how sAC can be inhibited by a drug [8, 9].…”
Section: Introductionmentioning
confidence: 99%